2021
DOI: 10.2754/avb202190010047
|View full text |Cite
|
Sign up to set email alerts
|

The effects of buccal administration of azaperone on the sedation level and biochemical variables of weaned piglets

Abstract: The aim of the study was to compare the efficacy of buccal and parenteral administration of azaperone in order to achieve pig sedation. The type of study was prospective randomized and double blinded. A total of 40 weaned piglets were divided into 4 groups (10 each) and monitored. Group A was injected intramuscularly (i.m.) with azaperone (Stresnil®, 40 mg/ml inj., Elanco Animal Health) at a dose of 2 mg/kg body weight (b.w.). Group B (control) was given 1 ml of saline buccally. Group C received a dose of 2 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The short-term effect may be limiting, for example, during prolonged transport or when used to reduce aggression and fighting between piglets after weaning (Tan and Shackleton 1990). Based on our previous study (Svoboda et al 2021), we hypothesised the possibility of achieving more effective and prolonged sedation in pigs by the oral administration of increased doses of azaperone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The short-term effect may be limiting, for example, during prolonged transport or when used to reduce aggression and fighting between piglets after weaning (Tan and Shackleton 1990). Based on our previous study (Svoboda et al 2021), we hypothesised the possibility of achieving more effective and prolonged sedation in pigs by the oral administration of increased doses of azaperone.…”
Section: Discussionmentioning
confidence: 99%
“…Mestorino et al (2013) showed that after the oral administration of azaperone, the concentration of azaperone in the analysed tissues did not exceed the maximum residue limit set by the EU. In our previous study (Svoboda et al 2021), we found that the oral administration of azaperone at a dose of 2 mg/kg orally induces sedation in piglets, but to obtain a clinically comparable sedation with an injection (2 mg/kg i.m. ), it is necessary to use a dose of 4 mg/kg b.w.…”
mentioning
confidence: 89%
“…Azaperone given alone by intramuscular route has a rapid onset of action (5-10 min) with a duration of action of 2-6 hours (maximal effects within 30 min), while intravenous injection often results in excitation [9]. Oral or intranasal administration of azaperone at a dose of 4 mg/kg induces sedation in piglets clinically comparable with an intramuscular administration of 2 mg/kg [38,39]. Deeper sedation with fewer adverse effects can be achieved by combining azaperone with ketamine and butorphanol [22,29] or azaperone with ketamine and an alpha-2 adrenergic agonist [30].…”
Section: Sedation and Premedicationmentioning
confidence: 99%
“…Azaperone given alone by the intramuscular route has a rapid onset of action (5-20 min) with a duration of action of 2-6 h (maximal effects within 30 min), while intravenous injection often results in excitation [9]. Oral or intranasal administration of azaperone at a dose of 4 mg/kg induces sedation in piglets that is clinically comparable to an intramuscular administration of 2 mg/kg [38,39]. Deeper sedation with fewer adverse effects can be achieved by combining azaperone with ketamine and butorphanol [22,29] or azaperone with ketamine and an alpha-2 adrenoreceptor agonist [30,40].…”
Section: Butyrophenonesmentioning
confidence: 99%